(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
3D printing or additive manufacturing (AM) is playing a critical role in clinical needs for on demand patient matched implants due to better functionalities and shorter lead time to manufacture. Establishing structure - process - property relationships for different AM techniques are vital and AM of multilaterals in single operation is also an exciting innovation. We use calcium phosphate (CaP) based 3D printed tissue engineering scaffolds, and surface modified hip and knee implant devices with controlled chemistry, mechanical strength, biological response, and degradation kinetics. Use of polymer helps in controlling drug release kinetics. In vitro and in vivo studies show improved osteogenesis, angiogenesis and controlled drug delivery using natural medicinal compounds (NMCs) in these 3D printed scaffolds and coatings. These systems are promising towards orthopedic and dental devices while eliminating the need for autografts or second site surgery for harvesting, as well as improving current hip and knee implant lifetime. Susmita Bose is a scientist and engineer, best known for her research on biomaterials, 3D printing or additive manufacturing of bone implants and natural medicine. She is the Herman and Brita Lindholm Endowed Chair Professor in the School of Mechanical and Materials Engineering at Washington State University. Prof. Bose’s interdisciplinary research interest lies at the interface of chemistry, materials science and engineering, bioengineering and biology, focusing on 3D printed bone tissue engineering scaffolds, surface modified implant materials and drug delivery vehicles. Her group has contributed towards synthesis and processing of calcium phosphate based bioceramics with controlled chemistry and degradation kinetics based on clinical needs, their mechanical and biological property evaluation.